Computational stress and modal analysis of car chassis - Mohamad Tarmizi, Arbain (2008)
Chassis is one of the important parts that used in automotive industry and every car passenger has it. This structure was the bigger component in the car and the car shape dependent to this chassis. As a major component of a vehicle, chassis has a considerable affected to the performance of the car. Also known as the “back bone” of the vehicle, it will be subjected to mechanical shocks, and vibrations and the result were the failures some component and resonant was the worst problem can be happened. Therefore, the prediction of the dynamic properties of the chassis is great significance to determine the natural frequencies of the structure to make sure working frequency are lower than natural frequency of the chassis to avoid resonant and determine the stress distribution on the chassis when receive the load. The finite element modeling issues regarding the experimental analysis of car chassis is addressed for the natural frequency analysis (modal) by using FEMPRO Algor. A comparison of modal parameters from experiment and computational shows the validity of the proposed approach. Result shows that 1st bending for 1st natural frequency (50.56 Hz), 1st torsion for 2nd natural frequency (62.10 Hz), mixed for 3rd natural frequency (83.25 Hz) and 2nd bending for 4th natural frequency (91.89 Hz). The model performed the linear material stress analysis to define the stress distribution on the chassis when receive the load and the maximum stress of all cases are normally acting upon at the point of joint part but the value is under the allowable stress for steel which is 300 MPa.